The governance of prevention in Italy - Antonio Boccia; Corrado De Vito; Carolina Marzuillo; Walter Ricciardi; Paolo Villari (Epidemiology, Biostatistics and Public Health)
After the political elections of February 2013, one of the tasks of the Ministry of Health of the new Government will be the development of the new edition – the third – of the National Prevention Plan (NPP), after the NPP 2005-2007 and the NPP 2010-2012. A brainstorming process about the recent experience of the NPP 2010-2012 is important not only to elaborate technical indications for new plan, but also to make some reflections on...